2006
DOI: 10.1002/ijc.21894
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating lymphocytes in seminoma lesions comprise clonally expanded cytotoxic T cells

Abstract: Seminoma lesions are characterized by a brisk inflammatory infiltrate containing both CD4 and CD8 T cells, which is of prognostic significance. However, whether seminoma cells express the HLA molecules required for classical T-cell recognition remains controversial. In the present study, we conducted a molecular, phenotypical and functional characterization of tumor infiltrating lymphocytes (TILs) from seminoma lesions. T-cell receptor clonotype mapping demonstrated the presence of clonally expanded T cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 35 publications
3
28
2
1
Order By: Relevance
“…Our data clearly support that the PD-1: PD-Ls interactions function as an inhibitory pathway on the lytic degranulation of Ag-specific CD8 ϩ T cells against M. tuberculosis, as illustrated by acquisition of CD107a/b expression. Given that the expression of CD107a/b has been described as a surrogate marker for cytolytic activity (18,54,55), we conclude that the PD-1 pathway would inhibit the cytotoxic activity against the pathogen. Accordingly, several groups have demonstrated that blocking PD-1:PD-Ls interactions in vitro reverses the exhaustion of HIV and hepatitis C virus-specific CD8 ϩ and CD4 ϩ T cells and restores cytokine production and proliferation (36, 38, 56, 57).…”
Section: Discussionmentioning
confidence: 80%
“…Our data clearly support that the PD-1: PD-Ls interactions function as an inhibitory pathway on the lytic degranulation of Ag-specific CD8 ϩ T cells against M. tuberculosis, as illustrated by acquisition of CD107a/b expression. Given that the expression of CD107a/b has been described as a surrogate marker for cytolytic activity (18,54,55), we conclude that the PD-1 pathway would inhibit the cytotoxic activity against the pathogen. Accordingly, several groups have demonstrated that blocking PD-1:PD-Ls interactions in vitro reverses the exhaustion of HIV and hepatitis C virus-specific CD8 ϩ and CD4 ϩ T cells and restores cytokine production and proliferation (36, 38, 56, 57).…”
Section: Discussionmentioning
confidence: 80%
“…Large, clear, neoplastic, primitive-type germ cells are consistently associated with a variable cytotoxic Tcell lymphocytic response 20 that helps to identify the tumor, even in cases with complex histology. Adequate fixation is important for a prima facie diagnosis, but often poor fixation destroys highly labile cells owing to a minimal amount of cytoskeletal fibrils.…”
Section: Dysgerminomamentioning
confidence: 99%
“…Atiprimod {2-(3-diethylaminopropyl)-8,8-dipropyl-2-azaspiro [4,5] decane dimaleate} has anti-inflammatory activities in animal models of rheumatoid arthritis and is well tolerated in phase I trials (61). Atiprimod also inhibits the proliferation of multiple myeloma cell lines in vitro by inhibiting signal transducer and activator of transcription 3 activation, thereby blocking the signaling pathway of IL-6, an important growth factor for multiple myeloma (62).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Chronic inflammation can be caused by infection, autoimmune disease, malignant and benign tumors, or other pathologies and results in the infiltration of inflammatory cells at specific sites in the body. These so-called tumor-infiltrating lymphocytes include macrophages (3), T cells, B cells, natural killer cells, neutrophils, and granulocytes (4,5). These cells excrete copious amounts of inflammatory cytokines into the microenvironment, including interleukin-6 (IL-6), IL-1a, IL-1h, tumor necrosis factor-a, and oncostatin M. For example, T lymphocytes and macrophages are the predominant inflammatory cells present in malignant prostate epithelium (4).…”
Section: Introductionmentioning
confidence: 99%